THE RELATIONSHIP BETWEEN SCHOOL RELATED VARIABLES AND MOTIVATIONAL PATTERNS OF UNDERGRADUATES: A LOGISTIC REGRESSION ANALYSIS - Can, Gurhan; Satici, Seydi Ahmet (UNIV CASTILLA-LA MANCHA, 2017)
The purpose of this study is to investigate the relationships between gender, academic achievement, and satisfaction with degree program, and motivational patterns of undergraduates. The sample of the study consisted of 259 participants 141 females, 118 males) who were defined according to their motivational patterns as having either autonomous motivation n=127) or controlled motivation n=132) among 732 participants who were selected randomly from the undergraduates attending Anadolu and Osmangazi Universities in Turkey. The data were collected via the Turkish Version of the Academic Motivation Scale. The findings obtained from 732 participants by using the linear regression analysis technique indicated that autonomous motivation predicted the academic achievement positively. The logistic regression analysis conducted on 259 participants also revealed that satisfaction with the degree program and being male increased the autonomous motivation significantly. The findings were discussed in the light of related literature.
Keywords: Motivational patterns; educational outcomes; logistic regression